Peta Perkembangan Wacana Intelektual Islam Nusantara Abad VII-XXI: Sebuah Analisis Historis - Muhammad Firdaus Imaduddin (Fakultas Adab dan Humaniora UIN Raden Fatah, 2021)
Basically, the development of Islamic intellectual discourse in the archipelago is can’t be separated from the gradual wave of Islamization by preachers from the outside, either from their status as traders, immigrants, or others. At the beginning of the arrival of Islam in the 7th century, intellectual traditions still seemed to be blurred and reaped the point of progress from around the 13th to the 21st. This article uses the historical method of thought Kuntowijoyo in an effort to explore in-depth studies regarding the dynamics of the flow of Islamic intellectual discourse in the archipelago. From the historical data analysis process, the result shows that the map of the development of the Islamic intellectual discourse in the archipelago can be classified typologically based on the period and the background of the area covering it, including: 1) early Islamic intellectual discourse in the archipelago (Mystic Islam 7th – 17th century ), 2) Islamic intellectual discourse during colonialism (traditional Islam versus modern Islam in the 16th - 19th century), 3) Islamic intellectual discourse in the period of independence (political Islam to cultural Islam in the 19th - 20th century), and 4) discourse Islamic intellectuals in the reform era (Right Islam and Left Islam 20th – 21st centuries).